COVID‐19 intensity across U.S. states and the liquidity of U.S. equity markets. Issue 2 (31st January 2023) - Baig, Ahmed; Berkowitz, Jason; DeLisle, Ronald Jared; Griffith, Todd
Abstract: We study the effects of COVID‐19 intensity on equity market liquidity across U.S. states. We exploit cross‐sectional variation in cases and deaths to investigate any association with the deterioration of stock liquidity of firms whose headquarters or operations are in the corresponding state(s). Our motivation stems from several underlying economic channels such as order processing costs, inventory costs, and adverse selection costs. We find strong negative relations between pandemic intensity and various intra‐day liquidity measures. Our results are more pronounced for firms operating in states with more stringent containment and health measures and within industries with greater risk exposure.